Comparative thermodynamic and techno-economic analysis of various medical waste-to-hydrogen/methanol pathways based on plasma gasification. (25th February 2023) - Li, Jiarui; Wang, Huating; Chen, Heng; Wu, Haoran; Xu, Gang; Dong, Yuehong; Zhao, Qinxin; Liu, Tong
Highlights: Three novel medical waste-to-hydrogen/methanol pathways based on plasma gasification. A comparative thermodynamic and techno-economic analysis is accomplished. The medical waste-to-hydrogen was more competitive in economic performance. The NPV sensitivity of the medical waste-to-methanol is better than other pathways. The medical waste-to-hydrogen & methanol showed more advantages in energy conversion and utilization. Abstract: Three novel medical waste-to-hydrogen/methanol pathways based on plasma gasification using Aspen Plus have been proposed: The first pathway is used to convert medical waste into hydrogen; the second pathway is applied to convert medical waste into methanol; the third pathway is used to convert medical waste into hydrogen & methanol. In this study, thermodynamic and techno-economic analyses were conducted to evaluate and compare the performance of three pathways. Furthermore, three schemes are assessed by comparative economic sensitivity concerning the chemical product price, electricity price, capital expenditure, and discount rate. The thermodynamic results show that process efficiency and process exergy efficiency of the third pathway can achieve 72.16 % and 66.88 %, which is higher than the first pathway (69.45 % and 65.65 %) and the second pathway (54.08 % and 50.93 %). The techno-economic results indicate that the first pathway has a shorter dynamic payback period of 3.83 years and a relatively higher net present value of 13, 783.57 k$ than the second pathway (7.42 years and 5, 700.32 k$) and the third pathway (5.27 years and 10, 780.00 k$). This work provides novel methods and guidance for efficient and economical harmless treatment and resource utilization of medical waste.